Enantiomeric analysis of simendan on polysaccharide‐based stationary phases by polar organic solvent chromatography. Issue 11 (17th May 2020) - Cheng, Lingping; Cai, Jianfeng; Fu, Qing; Ke, Yanxiong
Abstract: Herein, the enantiomeric separation of simendan by high‐performance liquid chromatography with ultraviolet detection using polysaccharide‐based chiral stationary phases in polar organic mode is described. Three chiral columns (Chiralpak AD‐H, Chiralcel OD‐H, and Chiralpak AS) were screened using pure methanol and acetonitrile without additives under isocratic conditions. A reversed elution order was observed on the Chiralpak AD‐H column when the methanol content in the mobile phase (methanol–acetonitrile mixtures) was above 10%, whereby levosimendan eluted prior to dextrosimendan. Further, it was found that increasing temperature effectively improved the enantioresolution on the Chiralpak AD‐H column. Van't Hoff analysis was performed to evaluate the contribution of enthalpy and entropy to the chiral discrimination process. The best enantioseparation ( α  = 3.00, Rs  = 12.85) was obtained on the Chiralpak AD‐H column with methanol as the mobile phase at 40°C. Thus, a quantitative method for the resolution of dextrosimendan was established and validated, which could be used as a reference for the determination of dextrosimendan in levosimendan products.